Two tales the wise king, & the story of maryam - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
The first tale follows a wise king whose fair decisions lead to prosperity for his kingdom. The second story recounts the life of Maryam, showcasing her piety, resilience, and the miraculous birth of her son, Essa.